Fatigue during the COVID-19 pandemic – prevalence and predictors: findings from a prospective cohort study - Kalfas, M; Ayling, K; Jia, R; Coupland, C; Vedhara, K; Chalder, T (Taylor and Francis Group, 2024)
The COVID-19 pandemic and consequent lockdowns had a substantial impact on mental health. Distress and fatigue are highly correlated. However, little is known about the determinants of fatigue in the general population during the pandemic. This study aimed to examine the prevalence and predictors of fatigue during the COVID-19 pandemic in the UK population. Online surveys were completed by a UK community cohort in April 2020 (wave 1), July-September 2020 (wave 2) and November-December 2020 (wave 3). In total, 3097 participants completed the wave 1 survey, and 1385 and 1087 participants (85.4% women) completed wave 2 and 3 surveys respectively. Fatigue was assessed using the Chalder Fatigue Scale at waves 2 and 3. Hair samples were provided by 827 participants (90.6% women) at wave 1 and wave 2, which were analyzed to indicate HairE (stress hormone). The mean total fatigue score during wave 2 was 14.7 (SD = 4.7), significantly higher than pre-pandemic levels observed in the community (mean difference 0.50, p = .003). At wave 2, 614 (44.3%) participants met the case definition for fatigue, only 15.6% of whom indicated that fatigue lasted for more than 6 months (suggesting it had started prior to the pandemic). Predictors of fatigue at wave 3 included being in a risk group, depression and belief in having COVID-19, which explained 23.8% of the variability in fatigue scores. Depression at wave 1 was the only significant predictor of remaining a fatigue case at wave 3. Fatigue was highly prevalent in the UK community during the COVID-19 pandemic and limited people’s daily function. Depression and sociodemographic variables were significant predictors of fatigue.